Determinants of Banking Stock Returns: The Moderating Role of Corporate Social Responsibility and Fraud Risk in Indonesian Banking - Sukma Rianti; Haryadi Haryadi; Afrizal Afrizal; Enggar Diah Puspa Arum (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the effect of financial performance, Enterprise Risk Management (ERM), government ownership structure, and Risk-Based Bank Rating (RBBR) on banking stock returns, with Corporate Social Responsibility (CSR) and fraud risk as moderate variables. The study is motivated by the volatility of the Indonesian capital market and inconsistent findings regarding the relevance of accounting information in emerging markets. This research employed panel data from 27 banking companies listed on the Indonesia Stock Exchange during 2015–2021. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) through the Panel EGLS approach. The results show that financial performance and ERM negatively affect stock returns, whereas government ownership structure and RBBR positively affect stock returns. CSR significantly moderates the relationship between ERM and stock returns (β = 0.251, p < 0.05) and between government ownership and stock returns (β = 0.314, p < 0.01). The findings indicate that investors perceive strict risk management and aggressive earnings strategies as signals of higher risk exposure and lower short-term growth prospects. In contrast, government ownership and RBBR strengthen investor confidence in institutional support, regulatory compliance, and financial stability. Furthermore, CSR and fraud do not directly affect stock returns but function contextually as moderating mechanisms. The novelty of this study lies in integrating RBBR into stock valuation models and revealing the asymmetric moderating role of CSR and fraud in the Indonesian banking sector. This study contributes to Signaling Theory and Agency Theory by demonstrating that investors in emerging markets rely more heavily on formal regulatory signals during periods of high fraud risk.